Internet as a Tool to Promote Women’s Entrepreneurship. Selected Aspects - Paulina Siemieniak; Małgorzata Rembiasz; Jakub Pawlak (Studia i Materiały)
The Internet is an important tool in the context of activity of women-entrepreneurs due to the possibility of flexible work organization, hence it facilitates the reconciliation of the parental role with professional activity. Therefore, it is advisable to study the awareness, the level of use and limitations on the use of various kinds of virtual tools and applications. This article is of a review and conceptual nature but also relies on the results of previous studies conducted by the authors.